TEACHERS' EDUCATIONAL QUALIFICATION, RANK LEVEL, WORKING DURATION, AGE, WORK MOTIVATION AND WORK EFFECTIVENESS - Bambang Budi Wiyono (Universitas Negeri Malang, 2016)
Teachers' Educational Qualification, Rank Level, Working Duration, Age, Working Motivation, and Working Effectiveness The study investigated the effects of educational qualification, rank level, working duration and age on the elementary school teachers' working motivation and working effectiveness. The sample of the study consisted of 438 elementary school teachers in Malang which were selected through cluster sampling technique. The study was conducted using explanatory design in the form of causal model. The data were collected using questionnaire and documentation, and were analyzed descriptively employing structural equation technique. The study revealed that that the effect of the educational qualification, rank level, working duration and age on teachers' working motivation and working effectiveness, both directly and indirectly, was not significant.